Study the Associations between Age and Levels of Glucose, Renal Function Tests in Type 2 Diabetic Patients. (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2021)
Background:Diabetic patients commonly suffer from some diabetic renal function disorder. Estimation urea and creatinine in the serum are considered as a good clinical indicators to assess glomerular filtration rate and renal function.  This study aimed to study the relation between the levels of serum glucose, urea and creatinine with type 2 diabetic patients and  their ages.Materials and Methods:The blood samples obtained from the participants when they attended AL-Hashymmia Hospital, Babylon, Iraq. About 50 patients who are subdivided according to the age into 4 groups are: 20-29 , 30-39, 40-49  and  ≥ 50 years old. Control group also included 50 healthy subjects and subdivided into the same above age groups.Results: The results show that there is a positive significant (P = 0.029 , r = 0.308 ) and highly significant (P=0.001 , r=0.728 ) correlation between each of the serum glucose level, serum urea level and the age of diabetic patients  respectively, but there is no significant correlation between level of serum creatinine and the age of diabetic patients as well as between all studied parameters related to control subjects  and their age.Conclusion: In diabetic patients the levels of serum glucose and serum urea increase with the progression of age which may result  more complications in diabetic patients, so it is necessary to give a super follow up to older diabetic patients.